2020
DOI: 10.1038/s41467-020-15240-w
|View full text |Cite
|
Sign up to set email alerts
|

Playing games with multiple access channels

Abstract: Communication networks have multiple users, each sending and receiving messages. A multiple access channel (MAC) models multiple senders transmitting to a single receiver, such as the uplink from many mobile phones to a single base station. The optimal performance of a MAC is quantified by a capacity region of simultaneously achievable communication rates. We study the two-sender classical MAC, the simplest and best-understood network, and find a surprising richness in both a classical and quantum context. Fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…MACs and their capacity regions have been studied in the early years of quantum information theory [7]- [9]. Recently, it has been shown that finding the capacity region even in that simplest scenario is NP-hard and that entanglement increases its classical capacity [10]. Here, we go beyond these results and consider the security aspects of MACs.…”
Section: Introductionmentioning
confidence: 97%
“…MACs and their capacity regions have been studied in the early years of quantum information theory [7]- [9]. Recently, it has been shown that finding the capacity region even in that simplest scenario is NP-hard and that entanglement increases its classical capacity [10]. Here, we go beyond these results and consider the security aspects of MACs.…”
Section: Introductionmentioning
confidence: 97%
“…Traditional studies of quantum-enhanced MACs have focused on the capacity rate region [27][28][29], which quantifies the optimal asymptotic communication rates between the senders and the receiver. From an information-theoretic sense, this is perhaps the most natural object to consider.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Boche and Nötzel [17] addressed the cooperation setting of a classical-quantum MAC with conferencing encoders, where the encoders exchange messages between them in a constant rate (see also [18]). Remarkably, Leditzky et al [19] have shown that sharing entanglement between transmitters can strictly increase the achievable rates for a classical MAC. The channel construction in [19] is based on a pseudo-telepathy game [20] where quantum strategies guarantee a certain win and outperform classical strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, Leditzky et al [19] have shown that sharing entanglement between transmitters can strictly increase the achievable rates for a classical MAC. The channel construction in [19] is based on a pseudo-telepathy game [20] where quantum strategies guarantee a certain win and outperform classical strategies. The authors of the present paper [21] have recently shown that the dual property does not hold, i.e.…”
Section: Introductionmentioning
confidence: 99%